1915
DOI: 10.1021/ie50077a012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Certain Organic Compounds on Wheat Plants in the Soil—Preliminary Paper.

Abstract: or without t h e persulfate treatment for steels of over 0. j o per cent carbon.T h e ferrous ammonium sulfate solution m a y be standardized against 0.1 N perrnanganatc, the strength of which has been determined with sodium oxalate. T h e iron value of the permanganate multiplied b y 0.917 gives the vanadium value. By this method t h e following results were obtained, the chromium in expts. 9, I O , 13 and 14 being added as KzCrlOl before the solution of the steel.T h e following steels were employed:-U. S . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1916
1916
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Fraps concluded that results from pot experiments differed markedly from those in aqueous culture. Funchess (1916) also reported on the effects of various supposed soil toxins in pot experiments with oats and corn and his results concurred, generally, with those of other workers (Dandeno 1910;Fraps 1915;Upson and Powell 1915). Lyon and Wilson (1921) attempted to confirm whether plant roots do indeed release organic matter and whether any of these substances do become oxidising or reducing.…”
Section: Substance Referencessupporting
confidence: 60%
See 1 more Smart Citation
“…Fraps concluded that results from pot experiments differed markedly from those in aqueous culture. Funchess (1916) also reported on the effects of various supposed soil toxins in pot experiments with oats and corn and his results concurred, generally, with those of other workers (Dandeno 1910;Fraps 1915;Upson and Powell 1915). Lyon and Wilson (1921) attempted to confirm whether plant roots do indeed release organic matter and whether any of these substances do become oxidising or reducing.…”
Section: Substance Referencessupporting
confidence: 60%
“…Fred (1912) found that "toxic" soil could not be amended through sterilising agents such as ether. Upson and Powell (1915) at the University of Nebraska investigated the effects of the putative toxins vanillin, salicyclic aldehyde, coumarin, quinone and dihydroxystearic acid in soil experiments but found little inhibition of seedling growth. Fraps (1915) found that dihydroxystearic acid administered at 500 ppm to corn and sorghum plants in pots had little effect.…”
Section: Substance Referencesmentioning
confidence: 99%
“…Work on soil aldehydes was taken up by several investigators (Davidson 1915;Fraps 1915;Funchess 1916;Upson and Powell 1915) and this work led to an understanding of the degradation of these compounds in soil (Gardner 1924(Gardner , 1926Robbins 1916Robbins , 1917Robbins and Lathrop 1919). Fred (1912) found that "toxic" soil could not be amended through sterilising agents such as ether.…”
Section: Substance Referencesmentioning
confidence: 99%